Three-dimensional hemisphere-structured LiSn0.0125Mn1.975O4 thin-film cathodes - Yim, Haena; Kong, Woo Yeon; Yoon, Seok-Jin; Nahm, Sahn; Jang, Ho Won; Sung, Yung-Eun; Ha, Jong-Yoon; Davydov, Albert V.; Choi, Ji-Won (ELSEVIER SCIENCE INC, 2014)
Three-dimensional (3D) high surface area LiSn0.0125Mn1975O4 thin film cathodes have been fabricated in order to increase a charge capacity in the Li-ion battery. Metal oxide films were deposited by RF magnetron sputtering on three types of hemisphere-structured templates fabricated via spin-coating with polystyrene (PS) beads. Compared to standard planar battery design, the capacities of the close-packed, linked, and isolated 3D films are higher by 1.4,2.6, and 2.1 times, respectively, which correlates with the corresponding increase of the specific surface area of the templates. The linked hemisphere cathode film shows an improved discharge capacity of 67.6 mu A h mu m(-1) cm(-2) without significant degradation of the cyclic retention. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: SPINEL LIMN2O4; LITHIUM; DEPOSITION; HOLLOW